Morning Glory Syndrome - Rashida Shabbir Tankiwala; Memuna Bahadur (Delhi Journal of Ophthalmology)
Morning glory syndrome is a congenital optic disc anomaly described by Kindler1 in 1970. It is a congenital funnel-shaped excavation of the posterior fundus that incorporates the optic disc, resembling the morning glory flower. Ocular complications may include strabismus, reduced visual acuity and retinal detachment and it may have systemic associations as in Aicardi’s syndrome. A patient with monocular morning glory syndrome and reduced visual acuity is reported. The pattern reversal visually evoked potential was reduced.